Analisis Keterkaitan Sektor Industri Pengolahan Terhadap Perekonomian di Provinsi Jawa Timur (Pendekatan Input Output) - Zahroo, Agustin Fathimatuz (Jurnal Ilmu Ekonomi JIE, 2022)
Against the Economy in East Java (Input Output Approach). Along with the rapid development of industrialization, the manufacturing sector has increased and shifted the agricultural sector. This article aims to examine the relationship between the manufacturing sector and other sectors in East Java Province and examine the impact of the manufacturing sector multiplier. Analysis of input output with secondary data Input Output. The results show that the manufacturing sector; service sector; agriculture, forestry and fisheries have forward linkages to the manufacturing sector. Furthermore, the information and communication sector; the accommodation and food and drink provision sector has backward linkages to the manufacturing sector. The output and labor multiplier is quite large compared to other sectors, while the income multiplier is larger than other sectors.